Rare anorectal malformations with long perineal fistula extending to the penile skin or scrotum: Clinical features and surgical pitfalls from a case series - Kazuki Shirane; Toko Shinkai; Hinako Sakai; Tomohiro Aoyama; Yudai Goto; Takato Sasaki; Naoya Sakamoto; Takahiro Jimbo; Yasuhisa Urita; Kouji Masumoto (Journal of Pediatric Surgery Open)
Background: A rare variant of male anorectal malformation characterized by a long perineal fistula extending to the penile skin or scrotum (LPF-PS) has been referred to using various diagnostic terms and remains poorly understood in terms of diagnostic methods and therapeutic strategies. Therefore, we clarified the diagnostic and surgical pitfalls of this variant. Methods: Boys with perineal fistulas who underwent neonatal anoplasty at the University of Tsukuba Hospital between January 2003 and June 2023 were enrolled. Patients were categorized into an LPF-PS group and a typical anocutaneous fistula group (control group) based on the fistula orifice. Demographic data, fistula length and distance to the urethra, surgical findings, and the postoperative course were retrospectively analyzed. Results: Eleven patients were identified (LPF-PS group, n = 4; control group, n = 7). The LPF-PS group had a longer operative time, longer hospital stay, and more severe complications (one urinary injury, two patients with significant blood loss, and one rectal wall injury) than the control group. Fistulography and urethrography showed that LPF-PS group had a longer median fistula length (LPF-PS vs control: 16.0 mm vs 7.0 mm) and a shorter median distance between the fistula and urethra walls (LPF-PS vs control: 4.5 mm vs 10.0 mm) than the control group. Conclusion: Early neonatal anoplasty for LPF-PS is associated with severe complications owing to the close proximity of the fistula to the urethra. Based on our results, accurate diagnosis based on fistulography, urethrography, and primary colostomy in the early neonatal period is highly recommended to avoid unnecessary complications.